A numerical model for explaining the role of the interface morphology in composite solar cells - Martin, C; Burlakov, V; Assender, H; Barkhouse, D (2007)
We have developed a numerical model that simulates the operation of organicinorganic photovoltaic devices. Using this model, we have investigated the effect of the interface morphology and have shown that for a given system, there is both a most efficient device thickness and the interfacial feature size for overall power conversion. The variation of current-voltage (I-V) curves with differing recombination rates, anode barrier height, and light intensity has been simulated with reducing the recombination rate and lowering the anode barrier height shown to lead to improved open circuit voltages and fill factors. Through this model, we show that the increase in fill factor observed when the lithium salt Li [C F3 S O2] 2 N is added to devices can be explained by an increase in the polymer hole mobility. © 2007 American Institute of Physics.